Financial Statement Fraud: Reviewed From Fraud Hexagon Theory with Audit Committee as a Moderating Variable - Eriyani, Evina Dwi; Rakhmawati, Ita (MALIA: Journal of Islamic Banking and Finance, 2025)
This study is an associative research aimed at exploring the influence of external pressure, rationalization, frequent number of CEO’s pictures, ineffective monitoring, change in director, and political connection on financial statement fraud, with the audit committee as a moderating variable. This research adopts a quantitative approach, where the data used are numerical and analyzed statistically to test the proposed hypotheses. The sample was selected using purposive sampling, resulting in 56 companies as research samples. The study was conducted by analyzing the annual financial statements of companies listed under the Financial Services Authority (OJK) for the year 2023. The data were obtained from the official OJK website (www.ojk.go.id), each company’s official website, online news sources, and other relevant references. The findings indicate that external pressure and rationalization have a positive influence on financial statement fraud. In contrast, the frequent number of CEO’s pictures, ineffective monitoring, change in director, and political connection have no significant effect on financial statement fraud. The audit committee is unable to moderate or weaken the influence of rationalization and change in director on financial statement fraud. The audit committee is able to moderate or strengthen the influence of external pressure, frequent number of CEO's pict’re, ineffective monitoring, and political connection on financial statement fraud.